Living Qur’an Surat At-Ṭalaq Ayat 7 terhadap Istri sebagai Pencari Nafkah dalam Rumah Tangga Kecamatan Barumun - Harahap, Fatimah Azzahro (Lembaga Yasin AlSys, 2023)
The Living Qur'an Study is a scientific study or research about various social events related to the presence of the Koran or the existence of the Koran in a particular Muslim community. Enliven the Qur'an through a continuous interaction. A living can be interpreted as a husband's obligation to his wife if this maintenance is properly provided for the wife, household needs and children's needs. It is clear that it is said that maintenance is the husband's obligation, then what if the wife is the one who earns a living in the household, and do the people who mostly earn a living are wives understand the meaning of Qs At-Ṭalaq verse 7. The method used is a descriptive qualitative research method. The preparation of this research using the type of field research (field research). Based on research, most wives who make a living in the household come from a lower-middle class economic perspective, while the influencing factors are a lack of knowledge, lack of religious knowledge and lack of awareness.